Problem Sosial Masyarakat Marginal Dalam Konsep Pewarnaan Lukisan Impresionisme - Merta, I Made Suka (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Human are individual as well as social beings. A social beings means that they live in the midst of others or living in a community defined as a society. Various social issues arise in the big city.  The development of a city brought many victims; the marginalized society is one of it.  The marginalized society is a group of people which are marginalized or excluded from the development, so they do not have any chance to obtain the benefit of the development. They frequently got systemic violence committed by the state (the authorizer).Those ideas then were manifested on an artwork of impressionism coloring concept. Impressionism is a style of painting which is characterized chiefly by concentration on the general impression of strong lighting, with emphasis on the color display and not the form. Specifically, the illustrated impression is the impression of light reflection on an object / invisible objects, especially sunlight because it has unlimited color richness. Colors used by the writer are mostly bold colors, i.e. bright colors. A bold black color is also used to create an atmosphere of misery, anguish, and gloom. Color used in the writer’s artwork is a description of few colors and displayed with an opaque technique / block.   Key terms: marginal, impressionism